Targeting choline phospholipid metabolism: GDPD5 and GDPD6 silencing decrease breast cancer cell proliferation, migration, and invasion. (30th June 2016) - Cao, Maria Dung; Cheng, Menglin; Rizwan, Asif; Jiang, Lu; Krishnamachary, Balaji; Bhujwalla, Zaver M.; Bathen, Tone F.; Glunde, Kristine
Abstract : Abnormal choline phospholipid metabolism is associated with oncogenesis and tumor progression. We have investigated the effects of targeting choline phospholipid metabolism by silencing two glycerophosphodiesterase genes, GDPD5 and GDPD6, using small interfering RNA (siRNA) in two breast cancer cell lines, MCF‐7 and MDA‐MB‐231. Treatment with GDPD5 and GDPD6 siRNA resulted in significant increases in glycerophosphocholine (GPC) levels, and no change in the levels of phosphocholine or free choline, which further supports their role as GPC‐specific regulators in breast cancer. The GPC levels were increased more than twofold during GDPD6 silencing, and marginally increased during GDPD5 silencing. DNA laddering was negative in both cell lines treated with GDPD5 and GDPD6 siRNA, indicating absence of apoptosis. Treatment with GDPD5 siRNA caused a decrease in cell viability in MCF‐7 cells, while GDPD6 siRNA treatment had no effect on cell viability in either cell line. Decreased cell migration and invasion were observed in MDA‐MB‐231 cells treated with GDPD5 or GDPD6 siRNA, where a more pronounced reduction in cell migration and invasion was observed under GDPD5 siRNA treatment as compared with GDPD6 siRNA treatment. In conclusion, GDPD6 silencing increased the GPC levels in breast cancer cells more profoundly than GDPD5 silencing, while the effects of GDPD5 silencing on cell viability/proliferation, migration, and invasion were more severe than those of GDPD6 silencing. Our results suggest that silencing GDPD5 and GDPD6 alone or in combination may have potential as a new molecular targeting strategy for breast cancer treatment. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Abnormal choline phospholipid metabolism is associated with oncogenesis and tumor progression. Gene silencing of the glycerophosphodiesterases GDPD5 and GDPD6 increased cellular glycerophosphocholine (GPC) levels in breast cancer cells. This GPC increase was more than twofold following GDPD6 siRNA treatment and marginal following GDPD5 siRNA treatment. GDPD5 silencing reduced cell viability/proliferation, and both GDPD5 and GDPD6 silencing decreased migration and invasion, suggesting that GDPD5 and GDPD6 targeting, alone or combined, may have potential as new treatment strategy for breast cancer therapy.